Influence of Adding Small Instream Wood on Fishes and Hydraulic Conditions in Channelized Agricultural Headwater Streams - Eric J. Gates; Peter C. Smiley (Fishes, 2024)
Instream wood is important for fish in headwater streams because it promotes the development of pool habitat and provides cover from predators during periods of low flow. The benefits of large instream wood (length > 1 m and diameter > 0.1 m) have been extensively documented, but little is known about the influence of small instream wood (length ≤ 1 m or diameter ≤ 0.1 m) on fish communities and hydraulic conditions (i.e., water depth, water velocity, wetted width, discharge, pool area) in channelized agricultural headwater streams in North America and Europe. Understanding the influence of small instream wood will provide information that can guide the development of novel management strategies for fishes within these degraded streams. We conducted a two-part field experiment in the summer of 2011 in channelized agricultural headwater streams in central Ohio, consisting of an initial instream wood survey to document the amounts and types of instream wood found in these streams, and then conducted a before–after–control–impact experiment where we sampled fishes and hydraulic variables before and after the addition of small instream wood to pools. The instream wood survey documented that instream wood density ranged from 0 to 0.29 pieces/m2, small simple pieces were the most frequently occurring type of instream wood, and parallel was the most frequently occurring instream wood orientation. The amount of instream wood was greater (p 0.450) in fish community structure or hydraulic variables occurred between control and treatment pools before or after the addition of small instream wood. Our results suggest the addition of large instream wood might be needed to elicit a fish community response, and it is possible to add instream wood to channelized agricultural headwater streams without impeding the downstream water flow.